THE PROBLEM OF HISTORICAL AND CULTURAL PROCESSES ON THE INTEGRAL CONCEPTTION OF PITIRIM SOROKIN - Victoria V. Vasilenko (Вестник Северо-Кавказского федерального университета)
In this article we can see the problems of correlations of historical and cultural processes. We can think so about the example of conceptions, famous Russian philosophers of 20th century P. Sorokin. They show us the vole of theories a historical and cultural progress in modern historical meaning.